The Case Study of International Transport by the Freight Forwarder in France - Iveta Kubasáková; Jaroslava Kubáňová; Patrícia Kollárová (Communications - Scientific letters of the University of Zilina, 2021)
The article presents an analysis of the freight forwarder and carrier costs on transport in chosen country of Western Europe. Costs of transport point out to several existing problems in this part of Europe. The case study is given that deals about chosen transport in France. The article contains a review of transport routes during 2019, which were performed by an international forwarding company. These sessions were carried out in problematic areas in France. These are the transport of refrigerated and frozen perishable goods. The shipments are realized between logistics centres in France. The high problem is with carriers, with qualifications of their drivers, the number of drivers and seasonality of the goods. The article describes these problems as dependences of the forwarder´s costs on individual transport routes. The article deals about more solutions, which could be used in this part of Europe.